Polymer nanocomposites based on functionalized carbon nanotubes - Siow Yi, Sam (2012)
The applications of polymer can be reached world widely including the thing we used to write, to wear, to communicate, to sleep and so on. Never imagine the day without polymer, whole world will stop moving without it. Nowadays, scientist and engineer are trying hard to make further improvement to the polymer properties such adding of nanofiller for better applications in human‟s life. Carbon nanotube (CNT) is an allotrope of carbon that found to be nanofiller that able to enhance the properties of original polymer. The objective of this research is to identify the improvement of the properties on polycarbonate (PC) by adding CNT as additive. The experimental parameters of this research included the composition of the CNT and treated CNT in matrix of PC. In this study, surface treatment that been carried on CNT is known as functionalized of CNT which to make the function of CNT in PC matrix become more apparent. There were two main research procedure which included sample preparation and characterisation based on the test that been carried out. Melt mixing technique by twin screw extrusion had been used for mixing and dispersion of CNT purpose. The samples in dumbbell shape that used in characterisation are been produced by using the injection moulding. The standard mould, ASTM D638 is been used as it is a standard dumbbell for mechanical testing. Several testing were carried out to characterize the properties of the sample that been produced, the testing included chemical resistance test, mechanical test and last but not least was weathering test. Some the pellet samples from twin screw extrusion were used for the chemical resistance test while others used to produce dumbbell sample for mechanical test and weathering test. The chemical resistance test was carried out by submerged the pellets sample into a beaker of chemical. While the mechanical test were carried out by universal mechanical testing machine, tensile strength and elongation of material were analysed based on the data obtained. Whereas the weathering test was carried out by using accelerated ultraviolet (UV)/ weathering system. One year period of UV exposed had been set and the changes in mechanical properties of the sample were investigated by the mechanical testing. Based on the result obtained, the properties of PC with treated CNT composite gave the most satisfied result. The addition of treated CNT not only improves the resistibility of PC towards chemicals, it also increases the mechanical properties and reduces the effect after weathered. The recommendation for future research of this topic is increase the amount of treated CNT in PC matrix which can give better reinforcement effect to PC.